PENERAPAN PENDEKATAN BERMAIN TERHADAP HASIL BELAJAR LARI SPRINT 50 METER PADA PESERTA DIDIK SMP - Khansa Dwi Pangesti; Ahmad Atiq; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem in this study is the learning outcomes of students are less than the maximum because there is no variation in the learning process of sprint running. This study aims to improve learning outcomes of sprint running using the playing approach in SMP Negeri 2 Pontianak. This research is a classroom action research / classroom action research. This study uses several stages, Cluster Sampling used and asessment .namely pre-cycle and then continued with cycle I and cycle II. As for the cycle, there are steps the researcher takes, namely planning, action, observation and reflection. The subjects in this study were students of class VII A in SMP Negeri 2 Pontianak. The research results obtained in the first cycle were 34.48% or as many as 10 students who were declared complete or scored above the KKM. In the first cycle as many as 65.52% or 19 students were declared unfinished. Because in the first cycle did not meet the success indicators of the study, which was 75% of all students who scored above the KKM, this study was continued to the second cycle. In the second cycle research, 82.76% or 24 students were declared complete or scored above the KKM, while 17.24% or 5 students were declared unfinished or had grades below the KKM. So it can be concluded that this class action research stopped in the second cycle because the achievement of the indicators of research success has been achieved that is equal to 75% of all students scored above the KKM.Keywords : Sprint Running, Approach to Play, Games